Urgensi Pemberitaan Injil Bagi Umat Pilihan: Suatu Kajian Tentang Relevansi Pemberitaan Injil Dengan Konsep Pilihan - Fitriani, Kristiana (JURNAL ILUMINASI, 2023)
A polemic in theological discussions is a matter of the relationship between God’s chosen people for saving and preaching of the gospel. God’s choice, we know election means the act of God’s choice in selecting and assign individuals who will be saved and become a member of the body of Christ. The basic of God’s choice is character of God, especially love, wisdom, sovereignty and omniscience of God. That is why God is never wrong choice and failed. If God has set His choice, then the preaching of Gospel is not needed anymore. But if preaching of gospel does not need not implemented yet, how about some parts of the Bible states that gospel should always be reported until the end of time. There is never a conflict in the truth and work of God. He has selected individuals to be saved, but the preaching of the gospel remains a very urgent to be implemented. God has determined that the preaching of the gospel to be a means for the people of his choice to fulfill the grace of God revealed in God’s choice.